Road pricing theory and practice - Lewis, Nigel C. (Thomas Telford, 1994)
This work describes the theory and practice of congestion charging using advanced electronic systems. This edition has been widely revised, updating the case studies and expanding coverage to include developments in the UK, Europe and the USA, providing up-to-date information in current theory and practice in congestion charging.